Pengaruh Leadership, Motivasi Dan Disiplin Dalam Berorganisasi Terhadap Komitmen Organisasi (Pada Himpunan Mahasiswa Kota Baru (HIMAKO) Malang) - Hasanuddin Hasanuddin; Hadi Sunaryo; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted at the Kotabaru Student Association in Malang City, which is a regional organization that accommodates South Kalimantan Kotabaru students who are actively registered in universities in Malang. The purpose of the study was to determine whether Leadership, Motivation and Discipline in Organizations Against Organizational Commitment. The type of research used was quantitative research with the method of distributing questionnaires. The sample in this study were 48 respondents and data processing using SPSS computer program. The variable used in this study is Organizational Commitment (dependent variable), while the independent variables are Leadership, Motivation and Discipline in Organization. This study has met the requirements of validity and reliability. Analysis of the data used in this study is the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination. Suggestions for further researchers who are interested in the same topic, it is better to do further research on other variables that can affect the organizational commitment variable, as well as examine more references to the factors that cause the decline in organizational commitment. Keywords: Leadership, Motivation, Discipline in Organization, Organizational Commitmen